2021
DOI: 10.31729/jnma.5545
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance to Escherichia coli among Urine Culture-Positive Patients in a Tertiary Care Hospital in Nepal: A Descriptive Cross-sectional Study

Abstract: Introduction: Urinary tract infection is treated by the antibiotic sensitivity pattern of uropathogensin our population. Present infection cases have been showing an increase in resistance to the currentfirst-line of antibiotics. The objective of this study is to determine the resistance of antibiotics inEscherichia coli in a tertiary care center. Methods: This is a descriptive cross-sectional study done in Kathmandu Medical College TeachingHospital from October 2018 to February 2019. The sample size was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Of the three aminoglycosides studied here, AMK showed the highest efficacy compared to GEN and TOB, supporting previous studies from USA [ 24 ] and Gabon [ 30 ]. However, a survey by Kushwaha et al [ 31 ] from Nepal showed an opposite result: GEN had higher efficacy against UTI-inducing E . coli isolates than AMK and TOB.…”
Section: Discussionmentioning
confidence: 99%
“…Of the three aminoglycosides studied here, AMK showed the highest efficacy compared to GEN and TOB, supporting previous studies from USA [ 24 ] and Gabon [ 30 ]. However, a survey by Kushwaha et al [ 31 ] from Nepal showed an opposite result: GEN had higher efficacy against UTI-inducing E . coli isolates than AMK and TOB.…”
Section: Discussionmentioning
confidence: 99%
“…3,6,7,41,59 The anatomical structure of women, such as the shorter urethra, being very close to the vagina and anal orifice, hormonal changes during the menopausal period, during sexual intercourse receiving bacteria from their partner, use of contraceptive materials, and involvement in sexual activities using both the vagina and anal orifice, might be the potential reasons for the higher prevalence of UTIs in female patients. 3,60 In addition, during pregnancy, numerous hormonal and mechanical changes in the body, glycosuria, aminoaciduria, and urine retention in the bladder contribute to a higher prevalence of UTIs in female patients. Thus, females are more susceptible to UTIs than males, as highlighted in the present study data.…”
Section: Discussionmentioning
confidence: 99%
“…These antibiotic susceptibility tests were consistent with prior studies. [19][20][21] This highlights the importance of conducting antibiotic susceptibility tests before prescribing treatment to ensure the appropriate choices of antibiotics.…”
Section: Discussionmentioning
confidence: 99%